A PENGEMBANGAN GAME EDUKASI PAKAIAN TRADISIONAL INDONESIA BERBASIS ANDROID - Ardian Arifin; Ferry Marlianto; Aris Budiman (Journal of Computer Networks, Architecture and High Performance Computing, 2019)
Culture in Indonesia has a lot of diversity. Indonesia which has many provinces also has many cultures. One of the cultures that exist in Indonesia is raditional clothing. Traditional clothing, a characteristic of adat and culture in each region and also used in each traditional ceremony. Along with the development of the times, the concern for the preservation of national culture, especially traditional clothing, was very minimal. For example, the lack of recognition and socialization of Indonesian culture in the community is one of the important factors why people's interest is lacking in traditonal clothing. This study aims to develop the development of an Android-based educational game on traditional Indonesian clothing. The method used in this study uses Research and Development methods. The results of this study were developed an educational game "Introduction to Traditional Clothing in Indonesia" on the Android platform that provides information to users about any traditional musical instruments in Indonesia. Educational games are expected to help in the introduction of existing cultures and can be used as a way to provide insight to children. From the results of testing carried out with the black box method, it can be concluded that this application can function well. And can provide users of Android smartphone games that are educational.Keywords: Educational Games, Traditional Clothing, Android Smartphones